Compartilhamento do conhecimento e o processo de orientação de discentes de pós-graduação stricto sensu - Rosilene Moreira Coelho de Sá (2015)
This research aims to understand knowledge sharing in the interactions of academic advising in master and doctoral level. It inquires what are the symbolic-affective elements involved in knowledge sharing inherent to the mentoring relationship established between teachers and students of post-graduate programs. The research subjects are professors and students of post-graduate programs with full mark in the Monitoring and Evaluation System of CAPES, from the field of Exact and Earth Sciences of a Federal University. The research is empirical, with qualitative approach, and descriptive. The data collection methods used are: interviews, guided by a predefined script, and Archetypal Test of Nine Elements - AT 9, which consists of making a drawing, describing it and answering a short questionnaire. The data raised through the interviews were conducted by content analysis, since the contents of the tests are designed to analyze subjectivity as a strategy to understand the supervisors point of view, as much as the student perspective. The research assumes that the conversion of tacit knowledge into explicit knowledge and vice versa occurs through a range of communication forms. This research aims to understand the aspects of knowledge management related to the creation, sharing and use of information in the interactions of academic advising in master and doctoral level. The identification and analysis of these interactions have the purpose to find out a better understanding of the dynamics of knowledge sharing in the construction of knowledge, in the scientific literature, as well as a deep observation of the behavior and of the relationship between supervisor and student. Furthermore, it intends to understand how these researchers use strategies, which were described and located within the knowledge management parameters, to organize and to advance in science.